Transcriptomic Analysis Provides Insights to Reveal the bmp6 Function Related to the Development of Intermuscular Bones in Zebrafish - Xu, Huan; Tong, Guangxiang; Yan, Ting; Dong, Le; Yang, Xiaoxing; Dou, Dongyu; Sun, Zhipeng; Liu, Tianqi; Zheng, Xianhu; Yang, Jian; Sun, Xiaowen; Zhou, Yi; et al. (Frontiers in Cell and Developmental Biology, 2022)
Intermuscular bones (IBs) are small, hard-boned spicules located in the muscle tissue that mainly exist in the myosepta of lower teleosts, which hurt the edibleness and economic value of fish. The study of the development of IBs is very important for freshwater aquaculture fishes but the molecular mechanism of its formation and the key regulatory genes remain unclear. In this study, we first constructed two types of zebrafish mutants (the mutants lost IBs and the mutants with partial deletion of IBs) by knocking out bmp6. We then carried out a transcriptomic analysis to reveal the role of bmp6 in the developmental mechanism of IBs, we used the caudal musculoskeletal tissues of these mutants and wild type zebrafish at three development stages (20dph, 45dph, and 60dph) to perform transcriptomic analysis. The results showed that the deficiency of bmp6 upregulated sik1 and activated the TNFA SIGNALING VIA NFKB pathway, which inhibited the development of osteoblasts and promoted osteoclasts’ formation, thereby inhibiting the formation of IBs. These results provided insights to understand the role of bmp6 in the development of IBs in zebrafish and are useful for selective breeding of IBs in cyprinids.